Quality of Financial Services Fund Distribution and Bank Channeling at PT. Pos Indonesia KCU Surabaya - Fotinus Wahyudi Josiriz; Reviandani, Oktarizka (Borong Newinera Publisher, 2024)
Currently the existence of PT. Pos Indonesia as a postal service provider is increasingly under threat because there are competitors who also provide similar services such as courier and logistics services and there are also quite a lot of assessments indicating dissatisfaction with the services provided. This fact encouraged PT. Post to continue to improve the quality of postal services, especially in financial services, Fund distribution and Bank channeling, so that it can continue to compete with competitors providing other courier and logistics services. The aim of the research is to describe the quality of Fund Distribution and Bank Channeling financial services at PT. Pos Indonesia (Persero) main branch Surabaya 60000. The type of research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions or verification. The theory used is the service quality theory of Zeithaml, Parasuraman and Berry (1990) (Hendrayady et al., 2020) which consists of: Tangible, Reliability, Responsiveness, Assurance, and Empathy). The research results show that the quality of financial services, Fund distribution and Bank channeling at PT. Pos Indonesia (Persero) Main Branch Surabaya 60000 can be said to be good because it provides a sense of comfort and satisfaction to service users. However, there are still several shortcomings related to the fact that there are still employees who do not use identification cards and queue numbers that are rarely used at bank channeling service counters.